2020
DOI: 10.1101/2020.04.20.051763
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structure-guided point mutations on FusionRed produce a brighter red fluorescent protein

Abstract: The development of fluorescent proteins (FPs) has revolutionized biological imaging. FusionRed, a monomeric red FP (RFP), is known for its low cytotoxicity and appropriate localization of target fusion proteins in mammalian cells but is limited in application by low fluorescence brightness. We report a brighter variant of FusionRed, FusionRed-MQV, which exhibits an extended fluorescence lifetime (2.8 ns), enhanced quantum yield (0.53), higher extinction coefficient (~140,000 M -1 cm -1 ), increased radiative r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…In the meantime, there are definite drawbacks which take from the value of FusionRed as a multipurpose fluorescence tag and call for further improvement of this RFP. Thus, an issue of the modest molecular brightness possessed by FusionRed has been extensively addressed in the elegant studies by the Jimenez lab, where both a directed evolution [17] and semirational design [18] were utilized to engineer the brighter variants of FusionRed (specifically, the FusionRed-MQV [19] shows ~4-fold brightness advantage over the parental RFP, though its emission peak has a 20-nm hypsochromic shift). The high-resolution spatial structure of FusionRed revealed that almost a half of its molecules carries an immature chromophore and possesses a protein backbone cleavage in a vicinity of the chromophore-forming amino acid triad [20].…”
Section: Introductionmentioning
confidence: 99%
“…In the meantime, there are definite drawbacks which take from the value of FusionRed as a multipurpose fluorescence tag and call for further improvement of this RFP. Thus, an issue of the modest molecular brightness possessed by FusionRed has been extensively addressed in the elegant studies by the Jimenez lab, where both a directed evolution [17] and semirational design [18] were utilized to engineer the brighter variants of FusionRed (specifically, the FusionRed-MQV [19] shows ~4-fold brightness advantage over the parental RFP, though its emission peak has a 20-nm hypsochromic shift). The high-resolution spatial structure of FusionRed revealed that almost a half of its molecules carries an immature chromophore and possesses a protein backbone cleavage in a vicinity of the chromophore-forming amino acid triad [20].…”
Section: Introductionmentioning
confidence: 99%